2014
DOI: 10.1136/gutjnl-2013-305418
|View full text |Cite
|
Sign up to set email alerts
|

Management of gastrointestinal and liver diseases during pregnancy

Abstract: In the majority of patients with chronic gastrointestinal and liver diseases, maintenance therapy is required during pregnancy to control the disease, and disease follow-up or disease control might necessitate endoscopy. Evidence on the safety of drugs and imaging techniques during pregnancy is scarce and sometimes difficult to interpret. In this review we summarise existing literature with the aim of optimising counselling of patients with common chronic gastrointestinal and liver diseases who want to conceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 129 publications
(115 reference statements)
0
31
0
4
Order By: Relevance
“…Other factors involved in pregnancy constipation are decreased colon motility, oral iron supplements, poor fl uid intake as a consequence of nausea, and pressure on the rectosigmoid colon by the gravid uterus in the third trimester, as well as functional bowel disorders [ 41 ]. Management usually involves reassurance and advice about increasing fl uid and fi ber intake, while laxatives are rarely required [ 17 ]. Moreover, dietary supplements of fi bers, as bran or wheat fi ber, are likely to help pregnant women experiencing constipation [ 37 ].…”
Section: Constipationmentioning
confidence: 99%
See 3 more Smart Citations
“…Other factors involved in pregnancy constipation are decreased colon motility, oral iron supplements, poor fl uid intake as a consequence of nausea, and pressure on the rectosigmoid colon by the gravid uterus in the third trimester, as well as functional bowel disorders [ 41 ]. Management usually involves reassurance and advice about increasing fl uid and fi ber intake, while laxatives are rarely required [ 17 ]. Moreover, dietary supplements of fi bers, as bran or wheat fi ber, are likely to help pregnant women experiencing constipation [ 37 ].…”
Section: Constipationmentioning
confidence: 99%
“…The clinical features of pregnancy-associated GERD do not differ from those seen in the general population, with predominant symptoms being heartburn and regurgitation, that aggravate following meals and when lying in a supine position. For women already diagnosed with GERD prior to pregnancy, symptoms often worsen as pregnancy progresses [ 17 ]. There are a number of functional and structural alterations that occur at the gastroesophageal junction during pregnancy that may at least explain the high prevalence of refl ux symptoms in this population.…”
Section: Gastroesophageal Refluxmentioning
confidence: 99%
See 2 more Smart Citations
“…In the pharmacologic treatment of diarrhea, which is more rarely seen than the other GIS diseases during pregnancy, the use of loperamide as a motility reducing agent, erythromycin, and ampicillin active ingredient if infection accompanies, should be evaluated by the physician. Although irritable bowel syndrome is rarely encountered during pregnancy, antispasm medications, tricyclic antidepressants, and selective serotonin reuptake inhibitors may be used for severe symptoms (44,46). In a study conducted, increased absorption of calcium and magnesium was reported due to the use of lactulose (47).…”
Section: Gastrointestinal System Drugsmentioning
confidence: 99%